Quantum wave packet calculation of reaction probabilities, cross sections, and rate constants for the C(1D) plus HD reaction - Gogtas, F; Bulut, N; Akpinar, S (Wiley, 2005)
The time-dependent real wave packet method has been used to study the C(D-1) + HD reaction. The state-to-state and state-to-all reactive scattering probabilities for a broad range of energies are calculated at zero total angular momentum. The probabilities for J > 0 are estimated from accurately computed J = 0 probabilities by using the J-shifting approximation. The integral cross sections for a large energy range, and thermal rate constants are calculated. (c) 2005 Wiley Periodicals, Inc.
Keywords: reaction dynamics; reactive scattering; C plus HD